Towards a One Environmental System in the Extractive Industries in South Africa: A critical analysis of its implementation date which may disturb its successful facilitation and exacerbate legal uncertainty in the industry - Gerber, Leonardus J. (University of Pretoria, 2019)
Mini Dissertation (LLM)--University of Pretoria, 2018.